Rapid fabrication of vascularized and innervated cell-laden bone models with biomimetic intrafibrillar collagen mineralization - Greeshma Thrivikraman (Nature Portfolio, 2019)
Bone tissue is a complex organic-inorganic nanocomposite and strategies that replicate the characteristics of bone tissue are scarce. Here the authors demonstrate the deposition of nanoscale apatite in collagen embedded with mesenchymal, vascular and nerve cells, using a protein-guided biomineralization approach.